ANALISIS AHWAL MUTAÊ½ALLIQÄ€T AL-FIÊ½LI PADA ALQURAN SURAH YASIN - Lidinillah, Rahma; Nurbayan, Yayan; Sopian, Asep (Jurnal Pendidikan Bahasa dan Sastra, 2019)
Based on the observation and interviews with Arabic Language students, it was founded that one of their lack of knowledge is about the meanings of conditions for the words that related to the verb, even this term is odd to them. The importance of this research lies in the introduction of the condition meanings for the words that related to the verb in a sentence. This study aims to find out the meaning of condition meanings for the words that related to the verb in The Koran Surah Yasin. This search uses a descriptive method of the content analysis model The verses of the Surah Yasin are the main source or primary data in this study while additional or secondary data in this study are books and journals. The results found that there were 40 words with 4 types of condition meanings for the words that related to the verb with details of 14 words discarding the subject (11 known meanings and 3 unknown meanings), 13 words discarding object (4 words explain the vague, 5 words occupying position intransitive verb because there is no connectionÂ  with established, 3 words guarding rhyme, and a word summarizing), 2 words prioritizing object (specializing and ruling out object), and 11 words prioritizing circumstance and jar majrur (6 words specializing, 4 words keeping rhyme, and a word occupies the denial position).